2012
DOI: 10.2174/092986712800784748
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-Mediated Drug Delivery in Cancer and Cardiovascular Diseases with Peptide-Functionalized Nanoparticles

Abstract: In recent years progress has been speeding in studies of cell-cell interaction governed by adhesion molecules, and in particular by integrins and their ligands in cells and in the extracellular matrix. Integrins are distributed in a variety of tissues and blood cells. An increased expression of integrins and of their adhesion counterparts is often observed in sites relevant to disease states. Important roles are played by integrin α(v)β(3) in cancer angiogenesis and metastatic diffusion, in angiogenesis in isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 273 publications
(404 reference statements)
0
41
0
1
Order By: Relevance
“…This study showed that over-expression of integrin α6 in HCC is a strong indicator for more aggressive tumors and poorer clinical outcome. All the currently available therapies for HCC are mainly oriented towards removing or destroying the tumors, whereas few therapies aim at blocking the process of HCC metastasis [24]. This study would help us to understand the metastatic process of HCC better and develop targeted molecular therapy to improve patients’ survival.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that over-expression of integrin α6 in HCC is a strong indicator for more aggressive tumors and poorer clinical outcome. All the currently available therapies for HCC are mainly oriented towards removing or destroying the tumors, whereas few therapies aim at blocking the process of HCC metastasis [24]. This study would help us to understand the metastatic process of HCC better and develop targeted molecular therapy to improve patients’ survival.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many efforts have been focused to develop integrin ligands to target integrin receptors in pathological states. 92 Peptide ligands can also be used for cancer diagnosis. For example, chlorotoxin, a peptide with a high selectivity for membrane-bound matrix metalloproteinase-2 (MMP-2), is over expressed in various cancers such as glioma, prostate and intestinal cancer.…”
Section: Cancer Therapeuticsmentioning
confidence: 99%
“…Integrins are key regulators of communication between cells and their microenvironment. They are directly involved in the interplay between pro-angiogenic growth factors and their receptors, thereby exercising varied biological functions such as cell adhesion, migration/invasion, proliferation, survival, and apoptosis [ 11 , 97 ]. Integrins are a set of heterodimeric transmembrane glycoproteins made up of different α and β subunits, and αvβ3-Integrin has received much attention as a potential anti-angiogenic target because it is upregulated in tumor-associated blood vessels [ 11 ].…”
Section: Discussionmentioning
confidence: 99%